Corneal Debridement Combined with Intrastromal Voriconazole for Recalcitrant Fungal Keratitis - Yajie Sun; Zhuo Sun; Yukai Chen; Guohua Deng (Journal of Ophthalmology)
Background. To analyze the therapeutic effects of corneal debridement combined with intrastromal voriconazole in recalcitrant fungal keratitis. Methods. This is a retrospective study. Fourteen patients with recalcitrant fungal keratitis were treated by corneal debridement combined with intrastromal voriconazole (50 μg/0.1 ml). This paper reviews and analyzes the patients’ basic state, surgical intervention, medicinal treatment, and outcomes. Results. The mean sizes of infiltration and ulcer were (5.54 ± 1.32)mm and (3.46 ± 1.03)mm, respectively, and the mean depth was (315.43 ± 57.72)μm. Twelve of the patients had satellite lesion, and 2 suffered hypopyon. After intrastromal voriconazole, the size of infiltration decreased significantly to (4.32 ± 1.10)mm (P<0.001), but there was no significant change in ulcer size ((3.36 ± 0.92)mm, P=0.082). Thirteen patients were cured after corneal debridement. The mean healing time was (15.38 ± 7.38) days. Excluding one cured patient with optic nerve atrophy and one patient for whom the treatment failed, the mean best-corrected visual acuity after healing was (0.23 ± 0.18)LogMAR, a significant improvement compared to pretreatment (0.87 ± 0.57(LogMAR), P=0.01). The mean corneal astigmatism was (1.3 ± 1.6)D of 12 cured patients after healing and (1.0 ± 0.7)D at final follow-up, and there was no significant difference (P=0.374). Conclusions. Corneal debridement combined with intrastromal voriconazole is a secure and effective treatment for recalcitrant fungal keratitis.